Batch Adsorption of Orange II Dye on a New Green Hydrogel—Study on Working Parameters and Process Enhancement - Andrei-Ionuț Simion; Cristina-Gabriela Grigoraș; Lidia Favier (Gels)
A new green hydrogel consisting of cherry stone (CS) powder and sodium alginate (SA) was synthesized through physical crosslinking. The product had a mean diameter of 3.95 mm, a moisture content of 92.28%, a bulk density of 0.58 g/cm3, and a swelling ratio of 45.10%. The analyses of its morphological structure and functional groups by scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) showed the successful entrapping of the CS in the SA polymeric matrix. The viability of the prepared hydrogel as adsorbent was tested towards Orange II (OII) anionic dye. The influence of the pH, adsorbent amount, contact time, and initial dye concentration was evaluated. Then, the impact of three accelerating factors (stirring speed, ultrasound exposure duration, and temperature) on the OII retention was investigated. The highest recorded removal efficiency and adsorption capacity were 82.20% and 6.84 mg/g, respectively. The adsorption followed Elovich and pseudo-second-order kinetics, was adequately described by Freundlich and Khan isotherms, and can be defined as spontaneous, endothermic, and random. The experiments confirmed that the obtained hydrogel can be used acceptably for at least two consecutive cycles, sustaining its effectiveness in water decontamination.